Knowledge, attitude and practice regarding dengue fever among general patients of a rural tertiary-care hospital in Sasaram, Bihar - Mohapatra, Sahana; Aslami, Ahmad Nadeem (International Journal Of Community Medicine And Public Health, 2017)
Background: Dengue fever (DF) is a rapidly spreading mosquito-borne viral illness all over the world. DF has expanded to new countries and from urban to rural areas. DF has emerged as a notable public health problem in recent decades. Rapid urbanization, environmental changes and neglected rural areas result in vector breeding which causes rise in dengue outbreaks. The objective of this study was to assess the knowledge, attitudes and practices (KAP) regarding DF among patients of a rural tertiary care hospital in Sasaram, Bihar. Methods:We conducted a hospital based cross-sectional survey among general OPD patients using a pre-designed questionnaire. The study was approved by institutional ethical committee. KAP assessment was done by a scoring system. KAP of DF among study population was represented as proportions (%). Results: Out of 223 individuals interviewed, 93% identified fever as a cardinal symptom of DF. The knowledge about other symptoms of DF was low among participants. Only 17.5% knew that DF is transmitted by Aedes mosquitoes. The correct timing of biting time was known by only 14%. Despite low knowledge, the participants had good attitude and most of them reported good preventive practices against dengue prevention and control. Conclusions:The knowledge of participants of our study was low and the attitude and practice was good in lieu of protection from other mosquito borne diseases. Therefore massive awareness campaigns are urgently required to protect the health of people against DF and to limit in future spread of DF in this part of our country.